Thermal coarsening of individual titanate nanowires and their assemblies: Surface vs. bulk diffusion. Issue 10 (July 2020) - Rossi, L.; Berdat, X.; Spina, M.; Brown, S.; Bernard, L.; Katrych, S.; Forró, L.; Horváth, E.
Abstract: The thermal coarsening of titanate nanowires was investigated from room temperature to 1000 °C by AFM, SEM, XRD and Raman spectroscopy. Phase transformation kinetics and the external morphology were studied in two configurations: i) as individual and suspended titanate nanowires on SiO2 surface (denoted as 2D geometry); and ii) as large assembly in form of sintered pellets (denoted as 3D geometry). The individual titanates nanowires were coarsened far below the melting temperature (1843 °C) of TiO2 and two temperature dependent geometrical transformation changes were identified. In the first one, the height decreases around 200 °C (~20% shrinkage) due to the dehydration of the layered titanate, followed by the titanate to anatase recrystallization until 600 °C. Interestingly, the surface area of the SiO2 supported high temperature stabilized individual nanowires increased or remained constant, which may be due to the topotactic effects and epitaxial strain stabilization. In the second one, at sintering temperature of 600–1000 °C, an intense nanowire coarsening was observed driven by a surface diffusion mechanism on substrate and a surprising stabilization of the anatase TiO2 . In the case of a 3D assembly of the nanowires the densification with significant particle coarsening is accompanied by the phase transformation from anatase to rutile around the known phase transition temperature. These results suggest that the surface area evolution of individual titanium oxide nanowires on SiO2 appreciably differs from the 3D assembly, and the surfaces may induce an extra stabilization effect and deviation from the classical Ostwald ripening surface diffusion model.